EXPLORING WRITING CHALLENGES FACED BY STUDENTS: STRATEGIES FOR ENHANCING WRITING SKILLS IN THE WRITING CLASS - Lina Farsia; Sarair (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study explores the experiences of Universitas Muhammadiyah Aceh third-semester English students, focusing on the difficulties they encounter and the methods they use to get better at writing. The study gathers students' opinions about the complex range of challenges they face in their writing classes, emphasizing problems with motivation, vocabulary growth, creative thinking, organizational abilities, and language mechanics (such as grammar and punctuation). Furthermore, a significant proportion of students confess that they are insecure about their writing skills. The study employs a qualitative methodology, with the main means of gathering data being questionnaires. There are twenty closed-ended, Likert-scaled questions in these surveys. To shed more light on the experiences of the students, in-depth insights are also obtained through interviews. Positively, the results show a trend, with many students actively seeking to improve through positive means. They use writing manuals and Internet resources, and they clearly want advice and criticism. In addition, they consistently engage in self-evaluation and reflection as well as writing workshops. These findings show that students are making an effort to improve their writing abilities, even though there are certain common issues. This study offers educators helpful advice by highlighting the importance of addressing motivational issues and offering tools to support students as they develop into competent English writers